(untitled) (Research, Society and Development, 2021)
Introduction: Early mobilization is a physiotherapy resource with a multi-professional approach that aims to decrease the physical and psychological effects that occur during long ICU treatment. Objective: Analyze the importance of the early mobilization techniques in patients in the intensive care unit affected by COVID-19 as well as the obstacles and hardships faced by the professionals who try to execute this type of intervention. Methods: Integrative review performed through a documental reading of articles found in the database of PubMed, VHL (Virtual health library), SciELO (Brazil Scientific Electronic Library Online), and Google Scholar, using the following keywords in the DeCS (Health science descriptors): Early mobilization; Intensive unit care; Physiotherapy and SARS-COV2. Results and discussion: To compose the discussion of this review, 10 articles that addressed early mobilization in patients affected by COVID-19 were selected according to the search criteria. The articles present that the use of early mobilization can directly impact the functionality of the patient, contribute to shortening the length of stay in hospital and decrease the use of invasive mechanical ventilation. However, obstacles such as sedation, hemodynamic instability, and the pandemic caused by COVID-19 have been a challenge to be overcome to execute the early mobilization in the ICU. Conclusion: Despite the evidence found about the benefits of early mobilization, there are still many barriers that prevent an efficient implementation of the intervention, limitations not only related to the patient but also related to the structure and organization of the team working in the ICU.